Estudios sobre los estilos conceptuales en un grupo de esquizofrenicos - Reyeros de la B., Maria del Socorro; Muro, Eduardo; Robles, Jesus; Lara Tapia, Luis (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A group of forty schizophrenics hospitalized in a psychiatric institution were studied regarding some aspects related to their cognitive styles and compared to three samples of normal school children to establish the relative level of psychological differentiation of the experimental group. The results suggest a “syndrome of low response” in the schizophrenic group who presented a greater number of analytical responses, as measured by the tests of conceptual style of Kagan, than the younger group in the control sample. These data show the coarctated character and poor discrimination of the schizophrenics before perceptual stimuli and bring us to face an interesting problem noted by this failure in perceptual organization. It has been considered by various authorities that the analytic-global dimension was the principle of cognitive control. It is expected that such processes explain in part the schizophrenics’ inadequacy in social situations and in relation to the “reality principle.”